(untitled) (Scientific journal of the Fergana State University, 2023)
This article is devoted to problems in the direction of improving the system of shaping and developing the creative activity of future teachers through person-oriented education, and in order to achieve efficiency in the direction of developing and improving the creative activity of future teachers of MTT content and essence, as well as the need to create necessary conditions for the manifestation of the creative, mental and intellectual potential of the subjects of pedagogical processes.